Access to Aid Data Transforms Lives - Wardhaugh, Alasdair (2012)
Aid transparency has emerged as a top priority for many donors who recognize that increasing access to aid information is central to improving the aid process. It increases accountability, helps countries make best use of scarce aid resources, increases the impact of aid in reducing poverty, improves lives in developing countries, and maintains domestic support for aid at times of financial stringency. That’s why the International Aid Transparency Initiative (IATI) was launched in Accra at the Third High Level Forum on Aid Effectiveness in September 2008 (HLF3). IATI is a multistakeholder voluntary initiative that seeks to improve the quality and use of international aid money by making aid information easier for people to find, understand, compare, and scrutinize.